Penilaian Interprofessional Collaboration pada Puskesmas dalam Upaya Penanganan Stunting di Sulawesi Barat - Mukhtar, Musdalifah; Risnah, Risnah; Irwan, Muhammad; Aslam, Nur Annisa; Ishak, Muhammad (Journal of Health Education and Literacy, 2023)
Stunting is one of the problems faced by Indonesia, which is a developing country. The implementation of interprofessional collaboration practices is still not carried out optimally by health workers, including nurses. This study aims to assess the implementation of Interprofessional Collaboration in handling stunting in West Sulawesi. This type of research is a quantitative research design with a descriptive analysis design with a cross sectional approach. The instrument used in this study was the Assessment of Interprofessional Team Collaboration Scale-II (AITCS-II) questionnaire. The results showed that the mean of the three indicators assessed, namely, partnership (3.97) cooperation (3.95), coordination (3.85), so that the overall assessment of the IPC (3.92) is in the category towards collaboration. Thus, it can be a concern for health service agencies to increase collaboration of health workers into good collaboration, especially in efforts to deal with stunting.